Embracing variety: how different perceptions of teacher wellbeing can contribute to enhanced work experiences - Benjamin Dreer-Goethe (Frontiers in Education, 2025)
IntroductionThe field of teacher wellbeing research is marked by a wide array of conceptual frameworks. These range from unidimensional models focused on stress or burnout to multidimensional models that encompass both positive and negative aspects. Some frameworks are adapted from work psychology, health psychology, or positive psychology, while others are specifically designed for the teaching profession. This diversity has been criticized for making it difficult to reach a consensus and compare findings, which limits the development of a clear understanding of teacher wellbeing and slows progress in making improvements. As a result, there is a growing call for unified approaches, either by merging models or developing integrated ones.MethodsThis conceptual analysis challenges the idea that the variety of frameworks is a problem for the field. Instead, it argues that this diversity can help create practical, actionable recommendations for improving teacher wellbeing. To illustrate this, three widely recognized multidimensional approaches to teacher wellbeing are explored: the Job Demands-Resources (JD-R) model, the PERMA model, and the concept of subjective wellbeing.ResultsThe findings suggest that the diversity in teacher wellbeing frameworks, rather than being a hindrance, can be a valuable resource.DiscussionThis analysis highlights the potential of a pluralistic approach to teacher wellbeing, suggesting that diverse frameworks can complement rather than contradict one another. By drawing from multiple models, stakeholders can design flexible, context-sensitive interventions. Future research should focus on developing guidelines for selecting and combining frameworks based on specific educational settings and goals.